О взаимосвязи языка и культуры : On the relationship of language and culture - Д.Д, Санжина (Mongolian Studies, 2023)
In this article, the author deals with the metaphorical transfer of names that helps mankind to know the reality, and creates a picture of the world, which varies from one culture to another, consequently, there are not either two absolutely identical etnolinguocultures or two absolutely identical pictures of the world. Because systems of things meanings, social attitudes, cognitive models become the base for worldview and understanding of every nation. Human consciousness is always ethnically determined. As known, functionally the most frequent words - the nouns and verbs usually accept metaphorizations.